Successful diagnosis and treatment of early splenic ectopic pregnancy: A case report. Issue 17 (April 2018) - Wu, Lan; Jiang, Xiaoqin; Ni, Juan
Abstract: Introduction: Splenic ectopic pregnancy (SEP), a special abdominal pregnancy, is extremely rare but carries a high risk of potentially uncontrollable, life-threatening intraperitoneal bleeding at early gestation, which is equivalent to the spontaneous rupture of the spleen. Therefore, early diagnosis of SEP is crucial and may avoid life-threatening situation. Case presentation: A 29-year-old G3P2 woman presented with 50 days of amenorrhea and positive serum β-human gonadotropin (β-HCG) was enrolled into the hospital due to the absence of gestational sac located in the uterine cavity. A pan-abdominal ultrasound scan revealed a 2.6 cm ×1.6 cm hyperechoic mass inferior to the spleen with color Doppler signal surrounding and 0.9 cm anechoic inside. The gynecologist found the gestational sac was located in the dorsal pole of the spleen through the exploratory laparoscopy. Total splenectomy was performed uneventfully to avoid the hemorrhage shock. The patient discharged with no complications and normal 1-month follow-up. Conclusion: It highlights that fully understanding of the knowledge about abdominal pregnancy, especially splenic pregnancy, and early imaging study with ultrasonography could reduce or avoid the misdiagnosis and miss-diagnosis of SEP.